Affective prosody and cortical activation in dementia of the Alzheimer’s type: an exploratory acoustic and fNIRS study - Oh, Chorong; Kim, In-Sop; Feltis, Ann (Frontiers in Dementia, 2025)
Affective prosody, the expression of emotion via speech, is critical for successful communication. In dementia of the Alzheimer’s type (DAT), impairments in expressive prosody may contribute to interpersonal difficulties, yet the underlying acoustic and neural mechanisms are not well understood. This exploratory study examined affective prosody production and cortical activation in individuals with DAT using a multimodal approach. Ten participants with DAT completed three speech tasks designed to elicit happy, sad, and neutral emotional tones. Acoustic features were extracted using Praat software, and cerebral hemodynamics were recorded using functional near-infrared spectroscopy (fNIRS), focusing on oxygenated (HbO) and total (HbT) hemoglobin levels across hemispheres. Multinomial logistic regression showed that initial fundamental frequency and speech rate significantly predicted emotional condition. Paired-sample t-tests revealed hemispheric differences in HbO and HbT during affective speech, particularly in the happy and neutral conditions. These findings suggest that individuals with DAT may exhibit reduced modulation of affective prosody and altered patterns of hemispheric activation during emotionally expressive speech. While preliminary and limited by the absence of a control group, this study highlights behavioral and neural features that may contribute to communication challenges in DAT and provides a foundation for future research on affective prosody as a potential target for intervention or monitoring.